Guest

If four points whose position vectors are a, b, c and d are coplanar, show that (a*b*c) = (a*d*b) + (a*d*c) + (d*b*c)

If four points whose position vectors are a, b, c and d are coplanar, show that (a*b*c) = (a*d*b) + (a*d*c) + (d*b*c)

Grade:12th pass

1 Answers

Gundeti Sailu
26 Points
one year ago
-3
IT is because that all are coplanar
{abc]=[bcd]=[cda]=[dab]
so by interchanging positions we get all=[-abc]

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free